A quantitative study of work values: perspectives of Vietnamese high school students - Ngo, Thanh-Thuy; Nguyen, Thang The (International Journal of Evaluation and Research in Education (IJERE), 2025)
In the context of Vietnam’s rapidly changing labor market, understanding the work values of youth has become essential for effective career guidance. By using a quantitative method to examine the work values of high school students in Vietnam, with a particular focus on the impact of gender differences. A sample of 544 students (327 female, 217 male) completing the work value questionnaire (WVQ), a validated instrument that underwent reliability testing and exploratory factor analysis (EFA) to ensure robustness. The WVQ, using a Likert scale from 1 to 5, assessed values including power (POW), benevolence (BEN), self-direction (SDI), tradition (TRA), and stimulation (STI). The results revealed that BEN and POW are dominated, with female students showing a greater inclination toward social values and self-assertive roles than male students do. BEN is received the highest mean score (4.09), followed by POW (4.03), while SDI, TRA, and STI are scored lower. These findings highlight the importance of aligning educational and career guidance programs with students’ core values, taking gender differences into account to create a supportive, inclusive environment for career decision-making. This research offers valuable insights for educators and policymakers, informing the development of vocational education strategies that are ensured by the diverse work value orientations of students.